The moderating influence of internship program on the relationship between undergraduates' perception and their intention to join tourism and hospitality industry: A theoretical model - Mohammed, Abdul Alem; Rashid, Basri (EconJournals, 2016)
A successful firm in the tourism and hospitality industry requires skilled and committed employees. However, in the current tourism and hospitality industry, the top challenge lies in the attraction and retention of qualified and skilled employees and a great proportion of the graduates fail to enter the industry.It is therefore important to provide a value conceptual model that expounds on the theoretical relationships existing between the perceptions of undergraduate students and their intention to join the industry.This study contributes to literature by clarifying the perceptions of students-intention to join the industry relationship and by determining the moderating influence of the internship program on such relationship.